Optimization of Water Quality Management on Growth Performance and Survival Rate of Vannamei Shrimp Litopenaeus vannamei at Marine Science Techno Park, Diponegoro University - Pratiwi, Rifqah; Windiarto, Arif; Tangguda, Sartika (Management Science Research Journal, 2023)
Water quality plays an important role in super-intensive vannamei shrimp cultivation because it can affect growth and survival performance, so its management needs to be considered optimally. Application of Bacillus subtilis bacteria can suppress the development of Vibrio sp. and also can stabilize plankton growth and maintain the balance of pond water quality. The purpose of this study is to determine the optimization of water quality management on the growth performance and survival rate of vannamei shrimp Litopenaeus vannamei at Marine Science Techno Park, Diponegoro University. This research method is a case study that includes interviews, observations, and following all stages in the process of vannamei shrimp production at Marine Science Techno Park, Diponegoro University. Water quality management in vannamei shrimp ponds includes treatments of water change, sipon, calcification, probiotics, and monitoring of water quality parameters. The results showed optimization of water quality management with the application of several routine treatments, showing temperature values of 26.50 – 28.80°C; pH 7.75 – 8.55; brightness 28.00 – 45.00 cm; salinity 10.00 – 35.00 g/L; dissolved oxygen 3.99 – 4.58 mg/L; alkalinity 134.00 – 164.00 mg/L; nitrite 0.00 – 0.60 mg/L; and water color ranges from light green, brown, brownish green. Optimization of water quality management in shrimp production with the application of several routine treatments can improve growth performance with ABW 17.91 g/ind, ADG 0.36 g/day, and survival 57.16% with a harvest size of 50 – 55.